Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Semarang Selatan - Vidia Mey Saroh; Juli Ratnawati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Low taxpayer compliance with tax responsibilities is the main cause of Indonesia's low state tax revenues. This research determines how taxpayer compliance is influenced by awareness, knowledge, and understanding of taxes and tax sanctions. The population is taxpayers registered at KPP Pratama South Semarang in 2021. Primary data processing uses the SPSS program, which is based on questionnaire responses from respondents. The reliability test, validity test, classical assumption test, F test, t-test, and analysis of the coefficient of determination are used as part of the data analysis process. The findings show how awareness, knowledge, and understanding of taxation, as well as sanctions, influence taxpayer compliance